Pelatihan Menggunakan Aplikasi Akuntansi Digital Sederhana (LAMIKRO) Pada UMKM Kabupaten Subang - Sri Mulyati; Icih Icih; Bambang Sugiharto; Daeng M. Nazier; Trisandi Eka Putri (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of the service is to educate and improve the quality of MSME business actors in Subang Regency in terms of bookkeeping, accounting records, and digital financial reporting through the LAMIKRO application. Thus, the financial statements prepared can be well organized. The method applied in this program begins with conducting interviews, observations and sharing knowledge about how to use a simple digital accounting application using the LAMIKRO application. The results of this service show that there are still many MSME actors who record financial statements manually, even some of them are still unable to make financial reports. Therefore, this service is carried out to facilitate the recording of financial statements for these MSME actors.